PENYIMPANGAN TAKSONOMI KATEGORI LINGUISTIK PADA SURAT LAMARAN KERJA MAHASISWA IKIP PGRI MADIUN (STUDI ANALISIS KESALAHAN BERBAHASA) - Meikayanti, Ermi Adriani; Kuswardani, Yuli (IKIP PGRI MADIUN, 2016)
There are many errors on Job Application Letter (JAL) as task of lecture. The errors can be analizyzed from the taxonomy of linguistic category consist of phonological, morphological,Â sintaxtical, semantical, and discoursial levels. Specifically, this research aims at explaining the data of errors, the classification of errors, the frequency of errors appearance, the cause of errors, the prediction of the levels in which the errors appeared, and the correction of JAL errors of IKIP PGRI Madiun students. This research is descriptive qualitative explaining the phenomena occurred on JAL of IKIP PGRI Madiun students. The qualitative data research and primary data source research are gained using writing document technique of students JAL. The validation datatechnique used are method and experts triangulations. The technique analysis data is error analysis procedure, consist of 1) collecting data of errors, 2)classifying errors, 3) classifying the frequency of error appearance, 4) explaining the cause of errors, 5) predicting the levels in which the errors appeared, and 6) correcting the errors. The result of this research shows that there are 26 similar errors of students JAL. The most frequency of errors appearance happened on words level.The cause of error is the students do not know the appropriate words that should be used in JAL. The errors appeared at the phonological, morphological, sintaxtical, semantical, and discoursial levels. The correction of errors have been done based on EYD, grammatical rule, and linguistics.There are many errors on Job Application Letter (JAL) as task of lecture. The errors can beanalizyzed from the taxonomy of linguistic category consist of phonological, morphological,sintaxtical, semantical, and discoursial levels. Specifically, this research aims at explaining thedata of errors, the classification of errors, the frequency of errors appearance, the cause of errors,the prediction of the levels in which the errors appeared, and the correction of JAL errors of IKIPPGRI Madiun students. This research is descriptive qualitative explaining the phenomenaoccurred on JAL of IKIP PGRI Madiun students. The qualitative data research and primary datasource research are gained using writing document technique of students JAL. The validation datatechnique used are method and experts triangulations. The technique analysis data is erroranalysis procedure, consist of 1) collecting data of errors, 2)classifying errors, 3) classifying thefrequency of error appearance, 4) explaining the cause of errors, 5) predicting the levels in whichthe errors appeared, and 6) correcting the errors. The result of this research shows that there are 26similar errors of students JAL. The most frequency of errors appearance happened on words level.The cause of error is the students do not know the appropriate words that should be used in JAL.The errors appeared at the phonological, morphological, sintaxtical, semantical, and discoursiallevels. The correction of errors have been done based on EYD, grammatical rule, and linguistics.